Information system for tourism activity monitoring and forecasting indicators as an experience for Portugal - Ramos, Célia M. Q. (2012)
In view of presenting the development of an information system (IS) associated with a real world case and an economic sector, namely tourism, the present article is the result of the methodological development of the scientific research study known as IMPACTUR - Tourism Activity Monitoring and Forecasting Indicators. The system that is the object of the current article is directed at tourism as an emerging sector of the economy geared towards excellence in some regions, thus requiring proper tools that allow decision-makers to acquire all possible slight advantages that are so essential to being the best. The IS formulated for IMPACTUR is one of these tools, innovative in Portugal and abroad, providing statistical information online related to tourism. It should be pointed out that it stores updated and timely information that is processed and made available in an electronic format via a website to all tourism professionals and researchers.